Spinopelvic surgical stabilization: a cases series - Matta Ibarra, Javier; Arrieta María, Víctor Elías; Torres Romero, Fernando; Avendaño Chacón, Napoleón; Escobar Abrego, Miguel; Andrade Rodríguez, Juan Carlos (Revista Colombiana de Ortopedia y Traumatología, 2014)
Background: Among the instrumentations that are performed on the spinal column, those of the cranial-cervical and spinopelvic region are the most complex stabilization methods used, given the biomechanical characteristics of these anatomical areas. Material and methods: A descriptive study of a sequential cases series is presented, which reviews the experience of the patients treated in the period 1992-2012, using spinal column to iliac or sacral (S1 and/or S2) fixations. An evaluation was performed using the demographics, clinical-surgical results according to indications, medical diagnoses, fixation methods used, anatomical extension of the construction in the spinopelvic segment, and complications associated with the technique. Results: A total of 169 spinopelvic instrumentations were performed on 103 men and 66 women, with a mean age of 37.4 years. The majority of the fixations were performed on the sacrum (153 cases [90.5%]) in patients with spondylitis, lumbar spinal narrowing, and spondylolisthesis. Less frequently were fixations to the iliac (14 cases [8.3%]) in patients with deformities, tumors, trauma, infections, and revision surgery. As complications, in order of frequency, were infections at the surgical site, material failures, or specific complications inherent to the underlying disease. Discussion: The results were similar to those found in the international literature reviewed as regards surgical indications, instrumentation techniques used, and post-surgical complications. In accordance with the case series analyzed, sacral (S1 and/or S2) fixation is recommended in degenerative disease (spondylolisthesis, spondylolysis, lumbar spinal narrowing), and iliac fixation (conventional Galveston, modular Galveston) in deformities, high energy trauma (lumbopelvic dissociations, L5-S1 inveterate dislocation fractures), and revision degenerative spine surgery (pseudoarthrosis, failure of osteosynthesis material, flat back). In diseases that selectively affect the lumbopelvic area (tumors, infections) sacral or iliac fixation must be chosen depending on the specific anatomical compromise.